2018
DOI: 10.1111/nyas.13653
|View full text |Cite
|
Sign up to set email alerts
|

The effects of verbal and spatial memory load on children's processing speed

Abstract: Examining the impact of maintenance on processing speed allows us to test whether storage and processing resources are shared. Comparing these relationships in children of different ages allows further insight into whether one or multiple resources for these operations must be assumed and whether remembering is proactive throughout childhood. We tested 185 4- to 6- and 8- to 10-year-old children using adaptive complex span tasks, in which simple judgments were interleaved between to-be-remembered items. The ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 55 publications
3
11
0
Order By: Relevance
“…Introducing four lead-in tone judgments clarified the cost of remembering an accumulating list of letters on judgment response times. Without lead-in judgments, we observed a nonlinear pattern of speeding and slowing on the judgments as the memory list accumulated, similarly to C. C. Morey et al (2018).…”
Section: Methodsmentioning
confidence: 62%
See 3 more Smart Citations
“…Introducing four lead-in tone judgments clarified the cost of remembering an accumulating list of letters on judgment response times. Without lead-in judgments, we observed a nonlinear pattern of speeding and slowing on the judgments as the memory list accumulated, similarly to C. C. Morey et al (2018).…”
Section: Methodsmentioning
confidence: 62%
“…While the first tone judgment (whether it was Lead-in-4 or Load-1) was always among the slowest, the other lead-in judgments were much faster, and comparable to the average response time on baseline trials. The best model revealed by a Bayesian ANOVA estimated using the BayesFactor R package (R. D. Morey et al, 2018; Rouder et al, 2012) with lead-in condition (with lead-in, without lead-in), serial position (restricted from Load-1 to Load-7), and list length (4, 5, 6, and 7) as within-participants factors performed on log-transformed trimmed response times included main effects of lead-in condition, serial position, and an interaction between lead-in condition and serial position, BF = 5.5 · 10 70 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Banbury and Jones (1999) found that speech interfered with visuospatial task performance despite being ignored. Studies have further confirmed that verbal and spatial activities interfered with each other under dual-task conditions, indicating the existence of a domain-general resource in the mental process of verbal and spatial (Vergauwe et al, 2010;Morey et al, 2018). Mobile phone use impaired driving safety, regardless of whether the phone was hand-held or hands-free (Strayer and Johnston, 2001).…”
Section: Relevant Theoretical Models: Impact Of Auditory Warnings On ...mentioning
confidence: 85%